2018
DOI: 10.3399/bjgp18x697997
|View full text |Cite
|
Sign up to set email alerts
|

The National CKD Audit: a primary care condition that deserves more attention

Abstract: Provenance Commissioned; not externally peer reviewed. 13. Kim LG, Cleary F, Wheeler DC, et al. How do primary care doctors in England and Wales code and manage people with chronic kidney disease? Results from the National Chronic Kidney Disease Audit. Nephrology, dialysis, transplantation 2017;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
(7 reference statements)
1
6
0
Order By: Relevance
“…Black patients have earlier onset ESKD (56.5 v 65.8 years) [ 56 ], and reduced pre-emptively listing for transplantation compared to White patients (odds ratio, 0.43) [ 54 , 55 ]. However in areas of high RRT uptake, rates of CKD diagnosis are low [ 57 ], which has also been reported in the USA, and overestimation due to eGFR equations in African Americans with ≥60 mls/min/1.73m 2 has been proposed to be contributory in keeping with our findings [ 37 , 56 , 58 61 ]. In a South African Black cohort approximately one in six patients would be not recognised as having CKD Stage 3 [ 36 ], and in a US cohort up to one in three Black patients were reclassified with a more severe CKD if unadjusted eGFR equations were used [ 60 ].…”
Section: Discussionsupporting
confidence: 89%
“…Black patients have earlier onset ESKD (56.5 v 65.8 years) [ 56 ], and reduced pre-emptively listing for transplantation compared to White patients (odds ratio, 0.43) [ 54 , 55 ]. However in areas of high RRT uptake, rates of CKD diagnosis are low [ 57 ], which has also been reported in the USA, and overestimation due to eGFR equations in African Americans with ≥60 mls/min/1.73m 2 has been proposed to be contributory in keeping with our findings [ 37 , 56 , 58 61 ]. In a South African Black cohort approximately one in six patients would be not recognised as having CKD Stage 3 [ 36 ], and in a US cohort up to one in three Black patients were reclassified with a more severe CKD if unadjusted eGFR equations were used [ 60 ].…”
Section: Discussionsupporting
confidence: 89%
“… 3 In CKD, the majority of people are managed in primary care rather than by kidney specialists. 4 Long-term CKD management requires a high level of patient engagement, both in decision-making and in the implementation of care. 5 For those with CKD, this encompasses a spectrum of behaviours ranging from adherence to medication and diet recommendations, maintaining physical activity, recognition and monitoring of risk factors (eg, blood glucose and blood pressure) and self-adjustment of home-care routines.…”
Section: Introductionmentioning
confidence: 99%
“… 8 As such there remains a need for better and innovative self-management interventions for those with CKD. 4 8 Digital self-management interventions have the potential to improve remote disease management and health outcomes 17 and are increasingly becoming integrated into self-management to improve behaviour. The COVID-19 pandemic has also presented those with long-term conditions and their healthcare teams an opportunity to innovate and move towards an increasingly digitalised care, with particular emphasis on supporting patients from their own homes.…”
Section: Introductionmentioning
confidence: 99%
“…A range of barriers have prevented widespread implementation of comprehensive education for people with CKD and a recent systematic review of self-management interventions in CKD found many interventions lack patient engagement in their design, and the majority of interventions do not apply behavioural change theory to inform their development 7 . As such there remains a need for better and innovative self-management interventions for those with CKD 3 7 . Digital self-management interventions have the potential to improve remote disease management and health outcomes 16 and are increasingly becoming integrated into self-management to improve behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…With less than 1% of time spent in contact with healthcare professionals, many patients are expected to self-manage their condition 2 . In CKD, the majority of people are managed in primary care rather than by kidney specialists 3 . Long-term CKD management requires a high level of patient engagement, both in decision-making and in the implementation of care 4 .…”
Section: Introductionmentioning
confidence: 99%